The Implementation of Gedsi in Teaching and Learning Activities at SD Muhammadiyah Malang Regency - Yuanka, Vania Puteri; Kumalasani, Maharani Putri; Ulum, Bahrul (JURNAL PAJAR (Pendidikan dan Pengajaran), 2025)
This study aims to evaluate the implementation of GEDSI (Gender, Disability, and Social Inclusion) in teaching and learning activities at SD Muhammadiyah Malang District. GEDSI is an inclusive approach that ensures that all students, regardless of gender, disability, or social background, get fair and equal access to education. This research method uses a qualitative approach with data collection techniques through classroom observation, interviews with students and teachers as the primary source of information, and strengthened by documentation of activities. The results showed that the implementation of GEDSI at SD Muhammadiyah Malang Regency was carried out through teaching modules, learning media, learner activity sheets, seating placement, and group division applied according to the character and needs of students, provision of inclusion-friendly facilities, and the implementation of SD Muhammadiyah Malang Regency succeeded in increasing students' awareness of gender and diversity issues. The contribution of GEDSI implementation is seen in the increased participation of students from various backgrounds, creating a more supportive learning environment.